Cervical Vestibular-Evoked Myogenic Potential (cVEMP) in adrenomyeloneuropathy patients. Issue 3 (March 2016) - Veciana, M.; Pedro, J.; Yagüe, S.; Pujol, A.; Casasnovas, C.; Papathanasiou, E.S.
Abstract : Objective: Adrenomyeloneuropathy (ADM) is one of the clinical phenotypes of adrenoleukodystrophy, characterized by distal axonopathy and varyng degrees of cerebral demyelination. cVEMPs, elicited by acoustic stimulation, are abnormal in several otovestibular disorders and brainstem lesions affecting the vestibulo-cervical reflex pathways. cVEMP have not been described so far in these patients. The aim of this study was to investigate cVEMP in ADM patients. Methods: We studied cVEMPs, brainstem auditory evoked potentials (BAEP) and motor evoked potentials (MEP) in 11 ADM patients. cVEMPs normal values were obtained from 10 healthy age-matched subjects. Results: BAEP and MEP were abnormal in all patients. cVEMPs had an increase latency in 10 tested ears, absent in 1, and normal in 11 ears. The mean latency of p13 was 16.06 ms (range: 13.6–21.8 ms). When responses were present in both ears for the same subject, no asymmetry ratio was detected in the corrected reflex amplitude. Conclusions: In contrast to BAEP and MEP that are severely affected in all patients, cVEMPs are only abnormal in 50% of patients. This shows relative sparing of the saccular neural pathway compared to the cochlear pathway and corticospinal tract. Key message: cVEMPs are abnormal in 50% of patients with ADM.